2022
DOI: 10.1186/s13073-022-01089-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of human non-small cell lung cancer by single-cell RNA-seq

Abstract: Background Lung cancer, one of the most common malignant tumors, exhibits high inter- and intra-tumor heterogeneity which contributes significantly to treatment resistance and failure. Single-cell RNA sequencing (scRNA-seq) has been widely used to dissect the cellular composition and characterize the molecular properties of cancer cells and their tumor microenvironment in lung cancer. However, the transcriptomic heterogeneity among various cancer cells in non-small cell lung cancer (NSCLC) warr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Li et al showed co-expression of lineage, however, bronchioid became overwhelmingly dominant and did not determine the lineage classification of patients. 56 In contrast, the transcriptional clusters allow for personalized therapies in identifiable lung cancer lineage. 7,8,9 Additionally, we compare correlation analysis of global, lineage-specific, our 42-classifier and immune pathways genes, separately ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al showed co-expression of lineage, however, bronchioid became overwhelmingly dominant and did not determine the lineage classification of patients. 56 In contrast, the transcriptional clusters allow for personalized therapies in identifiable lung cancer lineage. 7,8,9 Additionally, we compare correlation analysis of global, lineage-specific, our 42-classifier and immune pathways genes, separately ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the squamoid cluster may have the worst prognosis due to the hybrid state. 56 From the therapeutic aspect, the squamoid cluster may benefit from the MEK inhibitors after large-scale drug sensitivity analysis. Recently described dysregulation of CDKs in the neuroendocrine cluster, we further show that patients with high proliferation but low squamous and extracellular matrix remodeling may benefit from pan-CDK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, single-cell transcriptomic studies revealed substantial heterogeneity in cellular composition of the tumor microenvironment 8 , 46 , 47 and molecular properties in primary and metastatic LUAD. 48 , 49 Liu et al. demonstrated intra-patient and intra-tumor heterogeneity in the regulation of pathways related to LUAD tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Lineage plasticity, enabling the switch of cells from one phenotypic state to another, has been proposed as a source of ITH in cancer [ 48 ]. In primary NSCLC, both CNV and mitochondrial mutation-based lineage tracking analyses based on scRNA-seq data clearly showed that mixed-lineage and single-lineage tumor cells in the same patient originated from common tumor ancestors rather than from different origins [ 49 ]. Moreover, patients harboring high mixed-lineage features of different cancer subtypes had shorter survival.…”
Section: New Insights Into Cancer Immunotherapy Based On Ai-assisted ...mentioning
confidence: 99%